Estimation of H2S Produced from Reservoir Souring - Mahdi, Najwa H.; Al-Jawad, Mohammed S. (Journal of Petroleum Research and Studies, 2019)
The increase of the produce H2S due to water injection is known as reservoir souring. The sulfate reduced bacteria (SRB) which may be exist in the injected water reduces the sulfate which already existing in the reservoir. This study includes prediction of H2S for Mauddud reservoir in the Ahdeb oilfield by using specialized reservoir numerical simulator. Reservoir souring modeling utilized to enable operations to make better decisions for remedial actions to either prevent souring or to mitigate its impact. The aim of this study is to estimate the probability and timing of the start of H2S production in produced fluids. The results showed that the maximum concentration of H2S in the prediction production well was reached to 2.9 Ibm/day which occurs after 180 days this carry out when the SRB concentration was about 2000 ppm .The SRB concentration is increasing in areas where the sulfate is in high concentration and also there is a direct relationship between the SRB concentration and the H2S concentration